“Tell me another cowboy story” Western films in Chilean cinemas, 1935-1945 (Palimpsesto, 2016)
This paper analyses the way Chilean society inserted itself in a process of cultural dialogue with the United States, in which Hollywood –as a cultural industry- played the main role. I will study the reception of western films shown in cinemas in Santiago, through the examination of the films premièred from that genre. The research is framed between 1935 and 1945 because it was a period of particular relevance for the production of Hollywood westerns, and because the genre was very consolidated amongst Chilean audiences by those years.
Keywords: Mass culture; informal imperialism; Hollywood; westerns.